Analisis Jadwal Retensi Arsip Inaktif di Kementerian Pertanian Republik Indonesia - Sahry, Adelia Azahra; Marsofiyati, Marsofiyati; Maulida, Ervina (Jurnal Informatika, 2024)
This study aims to analyze the process of preparing, implementing, and addressing the obstacles in implementing the Inactive Archives Retention Schedule (JRA) at the Ministry of Agriculture, Republic of Indonesia. Inactive archives are documents that are rarely used, but they must still be managed according to regulations to prevent accumulation and ensure easy retrieval when needed. This research design used a qualitative approach with a case study design, allowing researchers to understand the problem in depth in a real-world context. Data were collected through observation, interviews, documentation, and questionnaires distributed to archives management staff. The results indicate that the JRA preparation has not been optimally implemented across all work units due to low employee understanding, minimal training, and limited resources. Furthermore, the JRA implementation is also less than optimal because many archives have not been adjusted to the applicable retention period. Therefore, strengthening regulations, regular training, and the formation of a dedicated archives team are necessary to ensure more effective and efficient archives management.